Research Status of Addition and Application of Different Rare Earth Elements in Laser Cladding and Their Effects on Properties and Structures - Li , Weibo; Sun, Siyuan; Han, Kai; Yang, Yong (International Journal of Materials Science and Technology Studies, 2024)
Laser cladding technology, as an efficient material surface modification technique, has seen widespread application in the industrial field in recent years. Rare earth elements, with their unique physical and chemical properties, have demonstrated significant advantages in laser cladding materials. Firstly, rare earth elements can significantly enhance the hardness, wear resistance, and corrosion resistance of the clad layer, thereby extending the service life of components. Secondly, rare earth elements can improve the micro-structure and bonding strength of the clad layer, enhancing overall mechanical performance. Additionally, rare earth elements can act as deodorizers during the laser cladding process, increasing the purity and quality of the cladding material. However, the addition of rare earth elements also brings some technical challenges, such as uneven element distribution and high costs. Currently, optimizing the application of rare earth elements in laser cladding to achieve a balance between material performance and cost remains a key research direction. Through further exploration and innovation, the potential of rare earth elements in laser cladding will be more broadly realized.